A SYK/SHC1 pathway regulates the amount of CFTR in the plasma membrane - Loureiro, Cláudia Almeida (2021)
Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene cause the recessive genetic disease cystic fibrosis, where the chloride transport across the apical membrane of epithelial cells mediated by the CFTR protein is impaired. CFTR protein trafficking to the plasma membrane (PM) is the result of a complex interplay between the secretory and membrane recycling pathways that control the number of channels present at the membrane. In addition, the ion transport activity of CFTR at the PM is modulated through post-translational protein modifications. Previously we described that spleen tyrosine kinase (SYK) phosphorylates a specific tyrosine residue in the nucleotide-binding domain 1 domain and this modification can regulate the PM abundance of CFTR. Here we identified the underlying biochemical mechanism using peptide pull-down assays followed by mass spectrometry. We identified in bronchial epithelial cells that the adaptor protein SHC1 recognizes tyrosine-phosphorylated CFTR through its phosphotyrosine-binding domain and that the formation of a complex between SHC1 and CFTR is induced at the PM in the presence of activated SYK. The depletion of endogenous SHC1 expression was sufficient to promote an increase in CFTR at the PM of these cells. The results identify a SYK/SHC1 pathway that regulates the PM levels of CFTR channels, contributing to a better understanding of how CFTR-mediated chloride secretion is regulated.